Nonlinear optical responses of carbon quantum dots anchored on graphene oxide hybrid in solid-state transparent monolithic silica gel glasses. (November 2018) - Zheng, Chan; Huang, Li; Guo, Qiaohang; Chen, Wenzhe; Li, Wei
Highlights: CQD/GO hybrid was introduced into solid-state matrices by sol-gel method. The practical application of CQD/GO SiO2 gel glasses in nonlinear optics was explored. The NLO performance of CQD/GO improved after incorporation into SiO2 gel glasses. The χ ( 3 ) of a CQD/GO hybrid in solid-state gel glasses was reported for the first time. Abstract: Exploring the nonlinear optical (NLO) response of graphene-based hybrids in solid-state three-dimensional macrostructures is vital to promote the practical development of graphene-based photonic and optoelectronic devices. Here, a solid-state hybrid of ultrafine and well-dispersed carbon quantum dots (CQDs) supported on graphene oxide (GO) was chosen as representative of such materials. The hybrid was introduced into organically modified silica gel glasses using a facile sol-gel wet chemical technique to obtain stable transparent monolithic nanocomposites, and their practical application in nonlinear optics was explored. The NLO performances were investigated by the open-aperture (OA) and closed-aperture (CA) Z-scan techniques in the nanosecond regime using a laser with a wavelength of 532 nm. The as-prepared CQD/GO SiO2 gel glasses displayed completely different NLO behavior from that of a CQD/GO suspension. The NLO performance of CQD/GO significantly improved after incorporation into SiO2 gel glasses because of the more graphitized structure of the CQD/GO hybrid. Both the OA and CA Z-scan patterns suggested that the NLO properties of the CQD/GO suspension combined nonlinear absorption and nonlinear scattering, while the NLO response of the CQD/GO SiO2 gel glasses stemmed primarily from nonlinear absorption and nonlinear refraction. In addition, this is the first report of the third-order nonlinear susceptibility χ ( 3 ) of a CQD/GO hybrid doped in solid-state gel glasses. The present results therefore demonstrate the feasibility and versatility of CQD/GO silica gel glasses, a promising new class of highly efficient NLO materials that can be applied in optical communications, radiofrequency optoelectronics, and all-optical signal processing.